MEKK1 Is Required for flg22-Induced MPK4 Activation in Arabidopsis Plants1[C][W] - Suarez-Rodriguez, M.C.; Adams-Phillips, L.; Liu, Y.; Wang, H.; Su, S.; Jester, P.J.; Zhang, S.; Zhang, S.; Krysan, P.J.
The Arabidopsis (Arabidopsis thaliana)gene MEKK1 encodes a mitogen-activated protein kinase kinase kinase that has been implicated in the activation of the map kinases MPK3 and MPK6 in response to the flagellin elicitor peptide flg22. In this study, analysis of plants carrying T-DNA knockout alleles indicated that MEKK1 is required for flg22-induced activation of MPK4 but not MPK3 or MPK6. Experiments performed using a kinase-impaired version of MEKK1 (K361M)showed that the kinase activity of MEKK1 may not be required for flg22-induced MPK4 activation or for other macroscopic FLS2-mediated responses. MEKK1 may play a structural role in signaling, independent of its protein kinase activity. mekk1 knockout mutants display a severe dwarf phenotype, constitutive callose deposition, and constitutive expression of pathogen response genes. This dwarf phenotype was largely rescued by introduction into mekk1 knockout plants of either the MEKK1 (K361M)construct or a nahG transgene that degrades salicylic acid. When treated with pathogenic bacteria, the K361M plants were slightly more susceptible to an avirulent strain of Pseudomonas syringae and showed a delayed hypersensitive response, suggesting a role for MEKK1 kinase activity in this aspect of plant disease resistance. Our results indicate that MEKK1 acts upstream of MPK4 as a negative regulator of pathogen response pathways, a function that may not require MEKK1's full kinase activity.